The impact of environmental regulation on water resources utilization efficiency - Wang, Qizhen; Wang, Shengyuan (Frontiers in Environmental Science, 2022)
With the rapid development of economy and the increase of population, water consumption has increased in China. Meanwhile, water waste, water pollution and uneven distributions of water resources have posed a great challenge to China’s economic development. Hence, the improvement of water resources utilization efficiency has become an important measure to solve the shortage of water resources. In this study, the super efficiency DEA model and Tobit model are adopted to study the impact of environmental regulation on water resources utilization efficiency. The results show that water resources efficiency score is different in different regions in China, where the efficiency score in the eastern region is the highest, followed by the western region and the central region. Environmental regulation negatively affects water resources utilization efficiency and these effects are different effects in different regions. Environmental regulation affects three variables, foreign direct investment, technological innovation, industrial structure, and then affects water resources utilization efficiency through these variables. Based on the above research, we put forward some policy recommendations for increasing environmental regulation intensity to improve water resources utilization efficiency.